Clinical, radiological, and laboratory features of HIV-negative pulmonary cryptococcosis with regard to serum lateral flow assay - Shi, Jiejun; Chen, Jianhua; Hu, Liqing; Song, Qifa; Qian, Guoqing (Frontiers in Medicine, 2024)
The number of figures and tables were 2 and 4 respectively. Clinical, radiological and laboratory features of HIV-negative pulmonary cryptococcosis with regard to serum lateral flow assay Abstract Cryptococcosis is the second most common invasive yeast infection in China. Pulmonary cryptococcosis (PC) is difficult to diagnose due to the lack of specific clinical features and the limitation of diagnostic techniques. Although lateral flow assay was very useful in diagnosing cryptococcal infection, quite a few patients with PC presented negative serum lateral flow assay (sLFA). Here, we conducted a retrospective study of HIV-negative patients who were diagnosed with PC in our hospital over the past decade to explore the potential relationship between the clinical profiles and sLFA in PC. 112 patients with sLFA tested were enrolled in this study, of which 58.93% were male. The positivity rate of sLFA for PC was 91.07%. The extent of pulmonary lesions was positively correlated with sLFA grade (Spearman r = 0.268, p<0.01). Solitary nodule (SN) and pneumonia were the most common imaging findings in PC with negative and positive sLFA respectively. Among 65 symptomatic PC patients, 14 presented with fever and had higher hypersensitive C-reactive protein (hsCRP) level and more extensive pulmonary involvement (Mann-Whitney U test, P<0.05) than those without fever. Symptomatic PC patients were more likely to have positive results of sLFA (Mann-Whitney U test, P=0.055) compared against asymptomatic ones. In conclusion, negative sLFA cannot exclude PC in patients with a solitary nodule in lung. Positive sLFA is more reliable in diagnosing PC in symptomatic patients with diffused lesions in lung who generally experience a more severe systemic inflammatory reaction.